Controlling Spatial Crystallization Uniformity and Phase Orientation of Quasi‐2D Perovskite‐Based Light‐Emitting Diodes Using Lewis Bases. Issue 3 (20th December 2019) - Han, Yaeeun; Park, Sungbin; Wang, Jian; Jariwala, Sarthak; Lee, Kangmin; Bischak, Connor G.; Kim, Sohyeon; Hong, Jungyun; Kim, Sunwoo; Lee, Mi Jung; Ginger, David S.; Hwang, Inchan
Abstract: Crystallographic orientation has a significant impact on the optoelectronic properties of films of quasi‐2D perovskite quantum wells. Here, oxygen‐bearing Lewis bases are employed as additives to explore their ability to modulate spatial uniformity of crystallization and orientation of crystal phases. Different Lewis bases added into the precursor solutions incorporating the large organic ammonium cation, phenethylammonium (PEA + ), lead to different crystallization kinetics, which are attributed to the varying stability of intermediate complexes. The microscopic photoluminescence heterogeneity and 2D X‐ray diffraction patterns of the thin films reveal that inclusion of Lewis bases can lead to spatially more uniform crystallization and random orientation, resulting in an enhancement in light‐emitting diode performance. In contrast, quasi‐2D phases formed without Lewis bases show poorer uniformity and preferentially vertical orientation. Comparing the Lewis base properties such as Mayer order unsaturation and polarizability suggests that the ability to weakly coordinate with lead and strongly interact with the large organic ammonium is a key factor in controlling the phase composition favorably toward highly luminescent light‐emitting diodes. This work may be of help to provide insight of what kinds of Lewis bases can be helpful to realize the desired phase composition for high performance of optoelectronic applications. Abstract : The effects of adding different Lewis bases on the composition of quasi‐2D crystal phases are investigated. The introduction of stable intermediate complexes not only enhances spatial uniformity of crystallization but also modulates the orientation. Weak dative bonding and strong hydrogen bonding combine to enhance device performance.